2015
DOI: 10.1038/ncomms8522
|View full text |Cite
|
Sign up to set email alerts
|

Associative memory realized by a reconfigurable memristive Hopfield neural network

Abstract: Although synaptic behaviours of memristors have been widely demonstrated, implementation of an even simple artificial neural network is still a great challenge. In this work, we demonstrate the associative memory on the basis of a memristive Hopfield network. Different patterns can be stored into the memristive Hopfield network by tuning the resistance of the memristors, and the pre-stored patterns can be successfully retrieved directly or through some associative intermediate states, being analogous to the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(139 citation statements)
references
References 38 publications
(40 reference statements)
0
138
0
1
Order By: Relevance
“…During the past decade, many scientists have shown a variety of methods of memristor application in hardware design of ANN systems. For instance, in [26] the hybrid CMOS-memristor Hopfield network-based associative memory is demonstrated. While in the work conducted by Guo et al [27], the CMOS-memristor hybrid architecture is applied in the design of 4-bit Hopfield neural ADC.…”
Section: Cmos/memristor Hybrid Network-based Adcmentioning
confidence: 99%
“…During the past decade, many scientists have shown a variety of methods of memristor application in hardware design of ANN systems. For instance, in [26] the hybrid CMOS-memristor Hopfield network-based associative memory is demonstrated. While in the work conducted by Guo et al [27], the CMOS-memristor hybrid architecture is applied in the design of 4-bit Hopfield neural ADC.…”
Section: Cmos/memristor Hybrid Network-based Adcmentioning
confidence: 99%
“…And the research on the application of memristors with the common synaptic plasticity in some kind of neural networks has also been conducted. For instance, HfO 2 -based memristors were used in a Hopfield neural network to implement associative memory [9]. The relationship between the resistance of the memristor and the synaptic weight was defined.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the resistance of the memristor and the synaptic weight was defined. And the resistances of the memristors were tuned to the target resistances through the application of the voltage pulses on the memristors as the training process [9]. Prezioso et al realized pattern classification by using the neural network based on memristors with synaptic plasticity [10].…”
Section: Introductionmentioning
confidence: 99%
“…The memristance of the memristor were used to calculate the synaptic weights in some cases. In 2015, Wang et al [5] Pavlov experiments showed relations between the memristors and the associative memory, also with the MHN [6] single and multi associative memories have been realised. Tarkov [7] in 2016 conducted experiments on the binary image convergence in associative memory.…”
Section: Introductionmentioning
confidence: 99%